PENGARUH KEPUASAN KERJA DAN KOMITMEN TERHADAP KINERJA KARYAWAN DI PT SARANA MULTI INFRASTRUKTUR (Persero) - Ilyas, Yasnimar; Harahap, Frans Hamzah (Economicus, 2022)
The purpose of this study is to determine the effect of job satisfaction and commitment on employee performance. The population in this study are all staff and superiors at PT. Multi-Infrastructure Facilities totaling 326 people, using the slovin formula, the number of samples obtained is 77 people. The data was obtained by distributing questionnaires. This type of research is Quantitative Causality. Data analysis uses SPSS version 23 program to test: Validity test, reliability test, normality, multiple regression, and t test and f test. The results of the study show that: (1) there is an effect of the satisfaction variable on performance, (2) that there is an influence of the commitment variable on performance, (3) the variable that has the most dominant influence on performance is the commitment variable, (4) there is a simultaneous influence ( together) and significant variables between satisfaction and commitment to performance, (5) the test of determination showed that the contribution of the variables of satisfaction and commitment to performance was 32%. From this value, it means that satisfaction and commitment variables affect performance quite moderately, namely 32%, while the remaining 68% is influenced by other factors not discussed in this study.